Before I was born : designed for parents to read to their child at ages 5 through 8 - Nystrom, Carolyn; Speidel, Sandra (Colorado Springs, Colo. : NavPress, 1995)
Explains, from a Christian perspective, the fundamentals of human sexuality emphasizing that sex is part of God's gift of marriage and family.
Keywords: Sex -- Religious aspects -- Christianity -- Juvenile literature; Providence and government of God -- Christianity -- Juvenile literature; Childbirth -- Religious aspects -- Christianity -- Juvenile literature; Sex instruction for children; Christian life; Childbirth -- Religious aspects -- Christianity; Providence and government of God -- Christianity; Sex -- Religious aspects -- Christianity; Juvenile works